Penerapan Media Pembelajaran Video Animasi Untuk Meningkatkan Keterampilan Memperkenalkan Anggota Keluarga Dalam Pembelajaran Bahasa Indonesia Pada Peserta Didik Kelas I SDI Alfattah Kecamatan Banjarsari Kota Surakarta Tahun Pelajaran 2020/2021 - Nurul Alimah (Universitas PGRI Semarang, 2020)
Nurul Alimah 20036102710124, Application of Animated Video Learning Media to Improve Skills to Introduce Family Members in Learning Indonesian to Class I Students of SDI Al Fattah Surakarta. This research is a classroom action research which aims to determine whether the use of animated video learning media can improve the skills to introduce family members in Indonesian language learning to the students of Class IB SDI Al Fattah Surakarta. The change target variable is the result of students' skills, while the action variable is the animated video media. The classroom action research consisted of three cycles. Each cycle consists of 4 stages, namely: planning, implementing actions, observing, and reflecting. The research subjects were 20 students of class 1B. Data collection techniques using tests, observation, and documentation. The data analysis technique used a qualitative analysis model. Based on the results of the study, it can be concluded that there is an increase in the skills to introduce family members in Indonesian language learning after implementing class actions with the application of animated video media. This can be shown by increasing the skills of students from cycle I to cycle III. In the first cycle the percentage reached 65% KKM. In the second cycle the percentage of achieving KKM was 85%. In the third cycle the percentage reached 95% KKM. Â Keywords: classroom action research, video animation media, skills, introducing family members